2021
DOI: 10.1007/s10804-021-09386-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Goal Appraisals and Goal Motivation on Dimensions of Identity Development: A Longitudinal Mixed Methods Analysis of European American Emerging Adults

Abstract: In the present study, we investigated the ways in which the ideographic goal descriptions and goal appraisals of European American high school seniors reflect potentials for intentional self-development during emerging adulthood (EA), a lifespan phase characterized by increasing levels of freedom and decreasing age-graded, socially sanctioned developmental norms. Additionally, we investigated whether variation in participants’ goal appraisals and the motivational qualities emergent in their goal descriptions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The characteristics of the university environment and the confluence of emerging adulthood [ 43 ] make it possible for young university students to be subjected to various stressors, such as the exploration of professional identity, family independence, a greater degree of autonomy and responsibility, exacting academic demands, or family and personal expectations [ 44 ]. Furthermore, a study by the World Health Organisation on the prevalence and distribution of mental disorders in first-year university students revealed that 1 in 3 students (31.4%) suffered some mental disorder in the first academic year at university and in 1 out of 5 cases (20.4%) the disorders caused developmental problems, not only at the academic level but also affecting social life, personal relationships and work [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the university environment and the confluence of emerging adulthood [ 43 ] make it possible for young university students to be subjected to various stressors, such as the exploration of professional identity, family independence, a greater degree of autonomy and responsibility, exacting academic demands, or family and personal expectations [ 44 ]. Furthermore, a study by the World Health Organisation on the prevalence and distribution of mental disorders in first-year university students revealed that 1 in 3 students (31.4%) suffered some mental disorder in the first academic year at university and in 1 out of 5 cases (20.4%) the disorders caused developmental problems, not only at the academic level but also affecting social life, personal relationships and work [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%